2021
DOI: 10.3390/jmse9121433
|View full text |Cite
|
Sign up to set email alerts
|

Multiaxial Fatigue Life Assessment of Integral Concrete Bridge with a Real-Scale and Complicated Geometry Due to the Simultaneous Effects of Temperature Variations and Sea Waves Clash

Abstract: In the present study, the authors attempted to predict the fatigue lifetime of a real-scale integral concrete bridge with H-shaped steel piles resulting from working and environmental conditions. In this regard, various types of nonproportional variable amplitude loads were applied on the bridge, such as temperature variations and sea waves clash. To this end, CATIA software was used to model the real-scale bridge with its accessories, such as a concrete deck, concrete anchors (walls), I-shaped concrete beams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…It is crucial to note that the increase in temperature not only diminishes the elastic modulus of the metal material but also attenuates its yield strength [18]. Consequently, both these material properties are dynamically adjusted with temperature variations [19], as comprehensively outlined in Table 1 [20]. The temperature referenced for the fracture mechanics properties of the deflector metal material is above 200 °C.…”
Section: Environmental Load Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…It is crucial to note that the increase in temperature not only diminishes the elastic modulus of the metal material but also attenuates its yield strength [18]. Consequently, both these material properties are dynamically adjusted with temperature variations [19], as comprehensively outlined in Table 1 [20]. The temperature referenced for the fracture mechanics properties of the deflector metal material is above 200 °C.…”
Section: Environmental Load Parametersmentioning
confidence: 99%
“…It is crucial to note that the increase in temperature not only diminishes the elastic modulus of the metal material but also attenuates its yield strength [18]. Consequently, both these material properties are dynamically adjusted with temperature variations [19], as comprehensively outlined in Table 1 [20]. The temperature referenced for the fracture mechanics properties of the deflector metal material is above 200 • C. In comparison, this study's maximum temperature on the lower surface was 132.2 • C. The actual temperature of the metal is lower than this, because this study measured the temperature on the backside of the insulation material.…”
Section: Environmental Load Parametersmentioning
confidence: 99%
“…A crack's "lifecycle", which culminates in fatigue failure of a cyclically loaded component, is divided into five stages: crack initiation, microstructurally short crack propagation, mechanically/physically short crack propagation, protracted crack propagation, and final structure fracture [122]. Since most industrial parts are under the effect of dynamic and repeating loads, the occurrence of fatigue phenomenon in the industry is inevitable [123][124][125][126][127][128]. In this regard, large industries such as petrochemical and power plants are not excluded.…”
Section: Fatigue Failurementioning
confidence: 99%
“…The most important achievement obtained in this research is the insight that the use of conical caps improves the fatigue life of a bridge by 45% compared to the use of vertical caps. Abdollahnia et al investigated the simultaneous influence of temperature changes and sea wave impact on the fatigue life of steel piles in integrated bridges [16]. They reported that in both loading modes, the critical zone, which is prone to failure, is the intermediate steel piles at approximately 1.5 m height from the floor.…”
Section: Introductionmentioning
confidence: 99%